Electrically Conductive and 3D‐Printable Oxidized Alginate‐Gelatin Polypyrrole:PSS Hydrogels for Tissue Engineering. Issue 9 (12th March 2021) - Distler, Thomas; Polley, Christian; Shi, Fukun; Schneidereit, Dominik; Ashton, Mark. D.; Friedrich, Oliver; Kolb, Jürgen F.; Hardy, John G.; Detsch, Rainer; Seitz, Hermann; Boccaccini, Aldo R.
Abstract: Electroactive hydrogels can be used to influence cell response and maturation by electrical stimulation. However, hydrogel formulations which are 3D printable, electroactive, cytocompatible, and allow cell adhesion, remain a challenge in the design of such stimuli‐responsive biomaterials for tissue engineering. Here, a combination of pyrrole with a high gelatin‐content oxidized alginate‐gelatin (ADA‐GEL) hydrogel is reported, offering 3D‐printability of hydrogel precursors to prepare cytocompatible and electrically conductive hydrogel scaffolds. By oxidation of pyrrole, electroactive polypyrrole:polystyrenesulfonate (PPy:PSS) is synthesized inside the ADA‐GEL matrix. The hydrogels are assessed regarding their electrical/mechanical properties, 3D‐printability, and cytocompatibility. It is possible to prepare open‐porous scaffolds via bioplotting which are electrically conductive and have a higher cell seeding efficiency in scaffold depth in comparison to flat 2D hydrogels, which is confirmed via multiphoton fluorescence microscopy. The formation of an interpenetrating polypyrrole matrix in the hydrogel matrix increases the conductivity and stiffness of the hydrogels, maintaining the capacity of the gels to promote cell adhesion and proliferation. The results demonstrate that a 3D‐printable ADA‐GEL can be rendered conductive (ADA‐GEL‐PPy:PSS), and that such hydrogel formulations have promise for cell therapies, in vitro cell culture, and electrical‐stimulation assisted tissue engineering. Abstract : Extrusion‐printed hydrogels are presented, which show enhanced electrical conductivity. Oxidized alginate‐gelatin hydrogel in combination with conductive polypyrrole polymer allows for the fabrication of 3D‐printed cell adhesive and electrically functional biomaterial scaffolds. Enzymatic and ionic crosslinking achieve material stability of 30 days in vitro. Together, this material can be used as a platform to study electrical stimulation assisted tissue engineering.